Inhibition by Argatroban, a Specific Thrombin Inhibitor, of Platelet Activation by Fibrin Clot-associated Thrombin - Lunven, Catherine; Gauffeny, Christiane; Lecoffre, Catherine; O’Brien, Donogh P; Roome, Nigel O; Berry, Christopher N (Thrombosis and Haemostasis, 1996)
Clot-associated thrombin retains amidolytic activity, and is resistant to inhibition by heparin, but not to low molecular weight thrombin inhibitors. We show that clot-associated thrombin induces platelet aggregation, is resistant to heparin:antithrombin III, less so to recombinant hirudin (rHV2Lys47) but not to argatroban, an active-site directed thrombin inhibitor. Fibrin clots prepared with human fibrinogen and thrombin were used to aggregate rabbit washed platelets assessed by single platelet counting, thromboxane B2 (TXB2) immunoassay and scanning electron microscopy. Fibrin clots decreased platelet counts, and released TXB2. Electron microscopy showed platelet aggregates on the clot surface. Argatroban concentration-dependently inhibited such aggregation with IC50s of 21 nM and 13 nM versus aggregation and TXB2 release respectively. The IC50s of Argatroban against fluid-phase thrombin producing similar aggregation were 12 nM (aggregation) and 33 nM (TXB2). rHV2Lys47 was less active against clot-induced aggregation (IC50 = 1.8 nM) than against fluid-phase thrombin (IC50 = 0.06 nM). Heparin had an IC50 of 0.02 mU/ml against aggregation induced by fluid-phase thrombin, but much greater concentrations are required to inhibit clot-induced aggregation (IC50 = 48 mU/ml). These data provide a basis for the superiority of direct-acting thrombin inhibitors over heparin in platelet rich thrombi.